Meshing Performance Analysis of the Cosine Roller Enveloping Hourglass Worm Drive - Xing Xincheng; Wen Yujie; Liu Zaixin; Sun Pengze (Jixie chuandong)
On the basis of the structure of the tapered roller enveloping hourglass worm drive, the cosine roller is obtained by changing the bus shape of the tapered roller. According to the principle of the meshing theory, the mathematical model of the worm pair is established, the meshing performance formula of the worm pair is derived, the meshing performance of the cosine roller worm pair and the tapered roller worm pair is compared by the Matlab software, the influence of the radius of the small end of the roller and the throat diameter coefficient on the meshing performance of the worm pair is analyzed, and the subsequent optimization design of the worm pair is provided as reference. The results show that the cosine roller enveloping hourglass worm drive has better lubrication performance than the tapered roller worm pair.